2021
DOI: 10.1007/s12630-021-02175-z
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 pandemic on intensive care unit workers: a nationwide survey

Abstract: Purpose To evaluate the impact of the COVID-19 pandemic on Canadian intensive care unit (ICU) workers. Methods Between June and August 2020, we distributed a cross-sectional online survey of ICU workers evaluating the impact of the pandemic, coping strategies, symptoms of post-traumatic stress disorder (PTSD; Impact of Events Scale-Revised), and psychological distress, anxiety, and depression (Kessler Psychological Distress Scale). We performed regression analyses to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 45 publications
2
50
0
3
Order By: Relevance
“…Nurses and physicians working bedside are directly exposed to the patients’ suffering, which may influence psychological distress, as Greenberg et al underline in their UK study (n = 709) [ 18 ]. In our study, to be a younger HCP was a comparable risk factor for symptoms, and the study from Metha et al [ 39 ] could confirm the results; however, the risk factor of being a less experienced HCP was not confirmed in the Canadian study. Less experienced nurses were found by Kramer et al [ 27 ] to experience psychological distress.…”
Section: Discussionsupporting
confidence: 55%
“…Nurses and physicians working bedside are directly exposed to the patients’ suffering, which may influence psychological distress, as Greenberg et al underline in their UK study (n = 709) [ 18 ]. In our study, to be a younger HCP was a comparable risk factor for symptoms, and the study from Metha et al [ 39 ] could confirm the results; however, the risk factor of being a less experienced HCP was not confirmed in the Canadian study. Less experienced nurses were found by Kramer et al [ 27 ] to experience psychological distress.…”
Section: Discussionsupporting
confidence: 55%
“…Therefore, the critical care educational experience of anaesthesia trainees seconded to the intensive care unit during the pandemic may not be as comparable in terms of diversity of pathology and patient mix as would be expected during non—pandemic rotations. Critical care exposure during this period may in fact have detrimental effects on trainees - there have been multiple documented impacts of the pandemic on intensive care staff indicating high levels of stress, depression, and burnout 28 , 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, majority of the research examined pandemic burnout focused on physicians, nurses and educators [e.g., ( 7 , 23 , 24 )], with only limited studies focused on the general public ( 7 ) and rarely addressed COVID-related burnout in relation to zero-COVID policy [e.g., ( 25 )]. It has been demonstrated that high levels of burnout are significantly associated with psychological burden, depression, anxiety and insomnia ( 7 ).…”
Section: Introductionmentioning
confidence: 99%